Double Filtration Plasmapheresis in the Treatment of Antineutrophil Cytoplasmic Autoantibody Associated Vasculitis With Severe Renal Failure: A Preliminary Study of 15 Patients. Issue 2 (7th March 2016) - Chen, Yinghua; Yang, Liu; Li, Kang; Liu, Zhengzhao; Gong, Dehua; Zhang, Haitao; Liu, Zhihong; Hu, Weixin
Abstract: Our aim was to investigate the clinical efficacy of double filtration plasmapheresis (DFPP) in the treatment of antineutrophil cytoplasmic autoantibody‐(ANCA) associated vasculitis (AAV) with severe renal involvement. Fifteen AAV patients who had severe renal failure (median SCr 5.6(IQR 5.2–9.0) mg/dL) and needed initial renal replacement therapy (RRT) were treated with DFPP and immunosuppressive therapy. Two plasma volumes were processed during each DFPP session. The changes of serum ANCA and renal function were investigated. After the DFPP treatment for three to five sessions, serum MPO‐ANCA level decreased from 250.0 ± 86.9 RU/mL to 70.5 ± 64.7RU/mL ( P =  0.00), with a median reduction rate of 67.6%. Eleven patients (73.3%) no longer needed from RRT 3 months after DFPP treatment, while another four patients remained on dialysis. During the follow up for median 10 (IQR 6–24) months, SCr level decreased to normal in one patient, one patient progressed into ESRD. The 1 year renal survival rate was 62.9%. Five (33.3%) patients were complicated with pulmonary infection. DFPP combined with immunosuppressive therapy could increase the renal recovery rate through rapidly decreasing serum ANCA levels for AAV patients with severe renal failure, but its clinical efficacy and impact on long‐term renal survival require further studies.